Potential of a Pluriversal Literacies Framework for Decolonizing English as Foreign Language (EFL) Policy and Practice in Colombia - Becerra Posada, Tatiana (Colombian Applied Linguistics Journal, 2024)
Literacy scholars have pointed out the neoliberal co-opting of literacy and language learning, specially when English is often promoted as the language of progress by the English language teaching industry and educational policies worldwide. This utilitarian discourse on English language learning has been passively accepted and reinforced by governments, policy makers, educators, and society in general. Such positioning not only furthers neoliberal values of competition and individualism, but also perpetuates Western ideas of development that have proven to be detrimental for our planet. Scholars in the field of Education have acknowledged the necessity of prioritizing indigenous epistemologies to transform education. Thus, in this article I introduce the ‘Pluriversal literacies’, a decolonial framework which conceptualizes literacies as relational, land-based, and multisentient practices, such as weaving plants, constructed within communities and their territories. I argue that this framework may facilitate the transformation of English language teaching, especially in foreign language contexts, by centering and valuing the knowledges, cultures, and literacies of non-dominant learners.